2019
DOI: 10.1039/c9ee00308h
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-induced 3D crinkled porous Ti3C2 MXene architectures coupled with NiCoP bimetallic phosphide nanoparticles as anodes for high-performance sodium-ion batteries

Abstract: Coupling NiCoP bimetallic phosphide nanoparticles with alkali-induced 3D crinkled Ti3C2 effectively enhances the structural stability and improved reaction kinetics of anodes for SIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
216
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 336 publications
(234 citation statements)
references
References 49 publications
9
216
0
1
Order By: Relevance
“…To date, MXenes have triggered continuous breakthroughs in many areas, including MXene antennas, MXene pen, MXene membrane, supercapacitors, and rechargeable batteries, to name just a few. There are also several reviews covering chemical composition, synthesis routes, unique properties, electrochemical and photocatalysis, and various biomedical applications of MXene .…”
Section: Introductionmentioning
confidence: 99%
“…To date, MXenes have triggered continuous breakthroughs in many areas, including MXene antennas, MXene pen, MXene membrane, supercapacitors, and rechargeable batteries, to name just a few. There are also several reviews covering chemical composition, synthesis routes, unique properties, electrochemical and photocatalysis, and various biomedical applications of MXene .…”
Section: Introductionmentioning
confidence: 99%
“…MXenes possess high electrical conductivity and allow easy ion intercalation between layers, leading to excellent performance as electrodes for electrochemical capacitors (supercapacitors) [ 80 ] and various kinds of batteries [ 81–85 ] However, the present reports on printing MXenes for energy storage nearly all focus on supercapacitors, with few studies on the lithium‐ion battery.…”
Section: Printing Mxenes For Various Applicationsmentioning
confidence: 99%
“…Interconnected architectures coupling conducting networks with enhanced physical entrapment of active materials are considered among the most promising candidates to promote the rate performance and energy density of LBs. [148,149] 3D carbon nanostructures such as carbon monolith, mesoporous carbon, porous carbon framework and corresponding nanocomposites owing to rich open space and exquisite hierarchical architectures, have enabled the development of LBs with higher energy density, lower cost, and stable performance. [150,151] It is demonstrated that the structural and interfacial design of 3D carbon nanostructures can not only establish favorable lithium reservoir but also enable lithium dendrite-free deposition.…”
Section: D Carbon Hierarchical Nanostructuresmentioning
confidence: 99%